1994
DOI: 10.1007/bf00198579
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural observations on anther tapetum development of freeze-fixed Ledebouria socialis Roth (Hyacinthaceae)

Abstract: Abstract. The tapetal ultrastructure of high-pressurefrozen, freeze-substituted Ledebouria socialis Roth (Hyacinthaceae) is described from the tetrad stage up to microspore mitosis. Cytoplasmic degeneration of the tapetum occurs after microspore mitosis. During the tetrad stage and the early free-microspore stage the tapetum cells appear to be meristematic; after callose dissolution they show an intense exocytosis of polysaccharides into the anther locule. Later, the tapetum cells are characterized by abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
(45 reference statements)
4
28
0
Order By: Relevance
“…Exine originates from the tapetal cells, and the altered exine ornamentation under HT stress is an indication of disruption to tapetal cells. Tapetal cells provide nourishment to the developing pollen, and early degeneration of tapetal cells under HT stress affects translocation of nutrients to the developing pollen grains, leading to loss of pollen viability (Hess and Hesse 1994). Saini and Aspinall (1982) showed that HT stress causes structural and functional abnormalities in reproductive organs, which leads to failure of fertilisation or premature abortion of seed.…”
Section: Discussionmentioning
confidence: 99%
“…Exine originates from the tapetal cells, and the altered exine ornamentation under HT stress is an indication of disruption to tapetal cells. Tapetal cells provide nourishment to the developing pollen, and early degeneration of tapetal cells under HT stress affects translocation of nutrients to the developing pollen grains, leading to loss of pollen viability (Hess and Hesse 1994). Saini and Aspinall (1982) showed that HT stress causes structural and functional abnormalities in reproductive organs, which leads to failure of fertilisation or premature abortion of seed.…”
Section: Discussionmentioning
confidence: 99%
“…The following procedures were used for processing of ultrathin sections: 1) overall staining with 0.5% weight/volume aqueous uranyl acetate and alkaline lead citrate (Reynolds, 1963); 2) periodic acid-thiocarbohydrazide-silver proteinate stained polysaccharides with 1-2 glycol groups (Thiéry, 1967;Courtoy and Simar, 1974;Erdos, 1986), as described previously (Hess and Hesse, 1994); 3) thiocarbohydrazide-silver proteinate staining, which indicated unsaturated lipids (Rowley and Dahl, 1977), as described previously (Hess and Hesse, 1994). Sections were examined with an electron microscope at 60, 80, or 100 kV (EM 10A, Zeiss; CM120 Philips, Eindhoven, Netherlands).…”
Section: Ultrathin Sectionsmentioning
confidence: 99%
“…We hate observed in very late stages of R. oficitialis tapetum maturation perfectly preserved organelles; this could, in part, be due to optimized fixation quality of this extremely fragile, delicate tissue. From recent investigations of secreting delicate tissues using advanced preparation methods (Hess &Hesse 1994, andRowley 1993, both for reviews) especially in the anther tapetum any not really adequate fixation and an item already pointed out by Carnie1 (1963) even a faint crushing of the anther during sample preparation may give rise to tapetal cell rupturing and to various cytoplasmic "artifacts". Such preparation artifacts may be similar to and sometimes hardly discernible not only from typical cytoplasmic structures appearing during genuine tapetum maturation but also from tapetum dysfunctions causing male sterility.…”
Section: Tapetummentioning
confidence: 99%
“…Interestingly this type of pollenkitt production is otherwise only found in some Orchidaceae with elastoviscin (a highly specialised pollenkitt-type) as pollen-connecting agent (Wolter et al 1988). In all other so far investigated angiosperm taxa plastids contribute substantially or even exclusively to lipid pollenkitt precursors (Weber 1992and 1996, Hesse & Hess 1993, Hess & Hesse 1994. At present in Lamiaceae only Rosiimriliirs is investigated in this direction.…”
Section: Tapetummentioning
confidence: 99%